Answer:
![x =-24](https://tex.z-dn.net/?f=x%20%3D-24)
Step-by-step explanation:
Given
![(\frac{2}{3})(\frac{1}{2}x + 12) = (\frac{1}{2})(\frac{1}{3}x + 14) - 3](https://tex.z-dn.net/?f=%28%5Cfrac%7B2%7D%7B3%7D%29%28%5Cfrac%7B1%7D%7B2%7Dx%20%2B%2012%29%20%3D%20%28%5Cfrac%7B1%7D%7B2%7D%29%28%5Cfrac%7B1%7D%7B3%7Dx%20%2B%2014%29%20-%203)
Required
Solve for x
![(\frac{2}{3})(\frac{1}{2}x + 12) = (\frac{1}{2})(\frac{1}{3}x + 14) - 3](https://tex.z-dn.net/?f=%28%5Cfrac%7B2%7D%7B3%7D%29%28%5Cfrac%7B1%7D%7B2%7Dx%20%2B%2012%29%20%3D%20%28%5Cfrac%7B1%7D%7B2%7D%29%28%5Cfrac%7B1%7D%7B3%7Dx%20%2B%2014%29%20-%203)
Open all brackets
![\frac{2}{3}*\frac{1}{2}x + \frac{2}{3}*12 = \frac{1}{2}*\frac{1}{3}x + \frac{1}{2}*14 - 3](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B3%7D%2A%5Cfrac%7B1%7D%7B2%7Dx%20%2B%20%5Cfrac%7B2%7D%7B3%7D%2A12%20%3D%20%5Cfrac%7B1%7D%7B2%7D%2A%5Cfrac%7B1%7D%7B3%7Dx%20%2B%20%5Cfrac%7B1%7D%7B2%7D%2A14%20-%203)
![\frac{2 * 1}{3 *2}x + \frac{2 * 12}{3}= \frac{1 * 1}{2 * 3}x + \frac{1 * 14}{2} - 3](https://tex.z-dn.net/?f=%5Cfrac%7B2%20%2A%201%7D%7B3%20%2A2%7Dx%20%2B%20%5Cfrac%7B2%20%2A%2012%7D%7B3%7D%3D%20%5Cfrac%7B1%20%2A%201%7D%7B2%20%2A%203%7Dx%20%2B%20%5Cfrac%7B1%20%2A%2014%7D%7B2%7D%20-%203)
![\frac{1}{3}x + \frac{24}{3}= \frac{1}{6}x + \frac{14}{2} - 3](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7Dx%20%2B%20%5Cfrac%7B24%7D%7B3%7D%3D%20%5Cfrac%7B1%7D%7B6%7Dx%20%2B%20%5Cfrac%7B14%7D%7B2%7D%20-%203)
![\frac{1}{3}x +8= \frac{1}{6}x + 7 - 3](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7Dx%20%2B8%3D%20%5Cfrac%7B1%7D%7B6%7Dx%20%2B%207%20-%203)
Collect like terms
![\frac{1}{3}x - \frac{1}{6}x =7 - 3 -8](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7Dx%20-%20%5Cfrac%7B1%7D%7B6%7Dx%20%3D7%20-%203%20-8)
![\frac{1}{3}x - \frac{1}{6}x =-4](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7Dx%20-%20%5Cfrac%7B1%7D%7B6%7Dx%20%3D-4)
Solve fraction
![\frac{2-1}{6}x =-4](https://tex.z-dn.net/?f=%5Cfrac%7B2-1%7D%7B6%7Dx%20%3D-4)
![\frac{1}{6}x =-4](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B6%7Dx%20%3D-4)
Multiply both sides by 6
![6 * \frac{1}{6}x =-4 * 6](https://tex.z-dn.net/?f=6%20%2A%20%5Cfrac%7B1%7D%7B6%7Dx%20%3D-4%20%2A%206)
![x =-4 * 6](https://tex.z-dn.net/?f=x%20%3D-4%20%2A%206)
![x =-24](https://tex.z-dn.net/?f=x%20%3D-24)
Answer:
The quantity of clover seeds in pounds to be added is 11.14
Step-by-step explanation:
Let
x -----> the quantity of poppy seeds in pounds
y -----> the quantity of clover seeds in pounds
we know that
-----> equation A
----> equation B
substitute equation B in equation A and solve for y
therefore
The quantity of clover seeds in pounds to be added is 11.14
The answer is 5.
you can turn it into a fraction ratio (6 over 15 is equal to 2 over c) and then cross multiply
They are selling the wrapping paper for $5 each and selling the foil wrapping for $7 dollars each.
39=5(5)+2(7)
57=3(5)+6(7)
Answer:
9n/60
Step-by-step explanation:
add 1/12 + 1/15 which = 5/60 + 4/60.
= 9/60
YAY!!!!!!!